Analisis Peran Artifical Intelligence pada Konten Tiktok @dimulai.id - Maria Indriani Kurnia; Detya Wiryani; Maudy Rizkiana Poedjadi (Jurnal Inovasi Komunikasi, 2024)
Current era of development, AI technology plays a big role in creating content in a short time. With the current AI technology, anyone can create an interesting content, because AI (Artificial Intelligence) technology, offers a new discovery when creating content on social media, this technology can also speed up the process of editing and creating content in the form of images, graphics, videos, etc..This research method uses Descriptive Qualitative method. This research approach is Phenomenology, which is the general focus of this research to examine/examine the essence or structure of experience into human consciousness by means of interviews.The role of AI (Artificial Intelligence) in content is to simplify and shorten the time in creating interesting and creative content. When explored more deeply, AI technology has many benefits and has a role in a content in the form of images or videos. This AI technology can make it easier for us to create interesting content, but keep in mind that applying it requires original creativity that comes from human ideas to create interesting content.